New Directions in Teaching Theatre Arts (Springer International Publishing, 2018)
This book reflects the changes in technology and educational trends (cross-disciplinary learning, entrepreneurship, first-year learning programs, critical writing requirements, course assessment, among others) that have pushed theatre educators to innovate, question, and experiment with new teaching strategies. The text focuses upon a firm practice-based approach that also reflects research in the field, offering innovative and proven methods that theatre educators may use to actively engage students and encourage student success. The sixteen essays in this volume are divided into five sections: Teaching with Digital Technology, Teaching in Response to Educational Trends, Teaching New Directions in Performance, Teaching Beyond the Traditional, and Teaching Collaboratively or Across Disciplines. Study of this book will provoke readers to question both teaching methods and curricula as they consider the ever-shifting arts landscape and the potential careers for theatre graduates.